Paget’s disease of bone: an osteoimmunological disorder? - Numan MS; Amiable N; Brown JP; Michou L (Dove Medical Press, 2015)
Mohamed S Numan,1,2 Nathalie Amiable,1 Jacques P Brown,1–3 Laëtitia Michou1–3 1CHU de Québec Research Centre, 2Division of Rheumatology, Department of Medicine, 3Department of Rheumatology, CHU de Québec-Université Laval, Quebec City, QC, Canada Abstract: Osteoimmunology represents a large area of research resulting from the cross talk between bone and immune systems. Many cytokines and signaling cascades are involved in the field of osteoimmunology, originating from various cell types. The RANK/receptor activator of nuclear factor Kappa-B ligand (RANKL)/osteoprotegerin (OPG) signaling has a pivotal role in osteoimmunology, in addition to proinflammatory cytokines such as tumor necrosis factor-α, interleukin (IL)-1, IL-6, and IL-17. Clinically, osteoimmunological disorders, such as rheumatoid arthritis, osteoporosis, and periodontitis, should be classified according to their pattern of osteoimmunological serum biomarkers. Paget’s disease of bone is a common metabolic bone disorder, resulting from an excessively increased bone resorption coupled with aberrant bone formation. With the exception of the cellular responses to measles virus nucleocapsid protein and the interferon-gamma signature, the exact role of the immune system in Paget’s disease of bone is not well understood. The cytokine profiles, such as the increased levels of IL-6 and the interferon-gamma signature observed in this disease, are also very similar to those observed in other osteoimmunological disorders. As a potential osteoimmunological disorder, the treatment of Paget’s disease of bone may also benefit from progress made in targeted therapies, in particular for receptor activator of nuclear factor Kappa-B ligand and IL-6 signaling inhibition. Keywords: Paget’s disease of bone, SQSTM1/p62, osteoimmunology, osteoclast, RANKL